Analysis Of The Characteristics Organizational Culture And Relationship With Performance Teacher In High School Pancabudi - Hasrul Azwar Hasibuan; Rindi Andika; Beautiful Fitri Yanti (INFOKUM, 2022)
The research was carried out with work procedures or stages starting from In the preparation stage the research team made preparations in the form of theoretical studies related to the research being carried out, discussions, sharing knowledge, and searching for literature were activities at this stage. Then make observations/preliminary observations of the problem, then ask questions in writing to the respondents in the form of a questionnaire then the data is collected, tested, analyzed, and evaluated.